Research on the dynamic evolution of logistics efficiency and its influencing factors in Guangxi - Luo, Yao; Huang, Peixing (Economics & Management Review, 2024)
Logistics efficiency is an important index to measure the development level of logistics industry. The author uses the data envelopment analysis ( DEA ) method to empirically analyze the logistics efficiency of Guangxi from 2012 to 2021. It is concluded that the non-DEA efficiency of Guangxi logistics efficiency is due to the redundancy of new fixed investment, logistics practitioners and highway mileage input, which does not exert the corresponding utility value, and the corresponding input factors should be appropriately reduced. According to the measurement results, and in view of the efficiency level of Guangxi logistics industry, some feasible and operable suggestions are put forward for the development of Guangxi regional logistics industry.